Expansion plugging material for leakage of cracks or karst caves

By using elastic steel wool balls and paraffin sealed elastic leakage plug spheres, combined with hydrogel water plugging agent, the problem of cracks or holes in drilling is solved, and efficient leakage plugging effect is achieved.

CN119505846AActive Publication Date: 2025-02-25SINOPEC OILFIELD SERVICE CORPORATION +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411669114.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25
Estimated Expiration
2044-11-21

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively solve the leakage problem caused by cracks or caves in drilling. Traditional leak-blocking materials are difficult to form a sealing layer in large caves, and high-concentration and large-grained materials are difficult to pump in through drilling tools, with a low success rate.

Method used

An elastic steel wool ball is used as the skeleton, and the diameter is reduced after compression, sealed in paraffin to form an elastic leakage plugging sphere. After the sphere naturally melts downhole, the steel wool ball returns to its original state, expands in volume, and accumulates in the leakage channel, forming a bridge structure that is not easily washed away, and is filled with hydrogel water plugging agent to improve the leakage plugging success rate.

Benefits of technology

The success rate of leakage plugging is improved, the elastic leakage plugging sphere can expand 8 to 27 times, forming a stable bridge structure, and the hydrogel water plugging agent has high strength and temperature resistance, effectively sealing the leakage and loss channels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses an expansion leaking stoppage material for crack or karst cave leakage, which comprises an elastic leaking stoppage ball body, the elastic leaking stoppage ball body adopts an elastic steel wire ball as a framework, and after the diameter of the elastic leaking stoppage ball body is compressed to 1 / 2-1 / 3 of the natural state, the elastic leaking stoppage ball body is sealed in paraffin. The preparation method comprises the following steps: firstly, respectively dissolving sodium alginate and polyvinyl alcohol, mixing, adjusting the pH value of the mixed solution to weak acidity, reacting with polyethylene glycol diglycidyl ether to prepare a multi-block copolymer, adding methanol, and stirring to prepare the hydrogel water shutoff agent. And mixing the mixture particles with triethanolamine borate and calcium lactate microcrystals, so as to prepare the high-strength interpenetrating network hydrogel water shutoff agent which is sensitive to calcium ions and borate ions at the same time. The leaking stoppage material can be easily fed to a leakage well section, can be highly expanded, and can easily stay in a leakage channel and be stacked to form a bridge structure, so that the leaking stoppage success rate is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a plugging material, in particular to an expansion plugging material for leaking in cracks or karst caves, and belongs to the technical field of plugging leaks in oil drilling. Background Art

[0002] Well leakage is a common worldwide problem in drilling projects, especially when drilling into faults, large cracks and karst caves. It is often manifested as loss of drilling fluid and inability to drill the next step. In this case, plugging the leakage requires a lot of materials and time, and sometimes even causes well wall collapse, drill sticking, overflow, blowout, etc. Some wells can only be abandoned and re-drilled. For example, in the Hubei Ebaye 1 well implemented in recent years, the drilling encountered karst leakage, and the whole well lost 27,850m of drilling fluid. 3 , consuming 1484t of plugging materials, 61.2d of loss time, and economic losses of more than 7 million yuan; Jiaoye 197-6FH well, lost water in the Hanjiadian Formation and Xiaoheba Formation, with a total of 38 plugging operations and 4834m of leakage. 3 , the loss time was 56.22 days, and the economic loss was more than 5 million yuan. In the Shengye 3-1 well in Nanchuan District, Chongqing, cracks and caves were encountered before 400-600m. Various measures such as plugging while drilling, gel plugging and cementing were used to plug the leak, but no obvious effect was seen. A total of 156,300 cubic meters of drilling fluid were lost, and it took 185 days to start the well. Finally, the well was forced to be abandoned, with an economic loss of more than 15 million yuan.

[0003] At present, there are relatively few plugging technologies and materials for cave-type leakage. Cement plugging is usually used. Conventional cement plugging has a certain effect on small caves, but when drilling into larger caves, it is necessary to increase the effectiveness of the bridge structure and a large amount of filling materials to form a plugging layer. Usually, gravel, wood chips and cottonseed shells are used. Although these materials are economical, the disadvantage is that it is difficult for bridge materials to form a plugging layer in large caves, and it is difficult to form an overall filling body after pouring cement. Sometimes chemical materials are also used for plugging, but the price of chemical plugging slurry is high and not suitable for large-scale use, and the effect is not good.

[0004] Summarizing the traditional plugging methods, the main reasons for the low success rate are as follows:

[0005] 1. Due to the relatively small inner diameter of the drill bit and the size of the drill bit water hole, the high-concentration, large-particle plugging material cannot be pumped through the drill bit to the lost well section;

[0006] 2. Large-particle plugging materials dropped from the wellhead are limited by the density and shape of the materials themselves, such as cottonseed shells, walnut shells, cement hemp ropes, etc., because of their low density and insufficient self-weight, they are slow to go deep, and some cannot even sink under their own weight; some materials, such as gravel and bricks, are irregular in shape and can smoothly reach the smaller well inclination section. If the well inclination is large, if the well inclination is greater than 30°, it is difficult to go down under their own weight, or even impossible to go down, and accumulate above the leaking well section, resulting in plugging failure;

[0007] 3. There is a lack of efficient filling materials between cottonseed shells, walnut shells and cement hemp ropes, which are easily washed away by the fluid in the leakage channel, resulting in a low success rate of plugging. Summary of the invention

[0008] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the abstract of the specification of this application and the title of the invention, and such simplifications or omissions cannot be used to limit the scope of the present invention.

[0009] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.

[0010] The purpose of the present invention is to overcome the problems existing in the prior art and provide an expandable plugging material for leaking in cracks or caves, which is easy to be delivered to the leaking well section, can be highly expanded, and can easily stay in the leaking channel and accumulate to form a bridge structure, thereby improving the success rate of plugging.

[0011] To solve the above technical problems, the present invention discloses an expansion plugging material for crack or cave leakage, comprising an elastic plugging sphere, wherein the elastic plugging sphere uses an elastic steel wire ball as a skeleton, and its diameter is compressed to 1 / 2 to 1 / 3 of its natural state and then sealed in paraffin.

[0012] Furthermore, the preparation method of the elastic leak-proof sphere is as follows: select steel wool of appropriate specifications, heat and melt paraffin, then immerse the steel wool in the melted paraffin liquid, and use a spherical mesh mold to compress it into a spherical shape. After the paraffin cools to room temperature and solidifies, take it out together with the mold, and demold it after cooling.

[0013] Furthermore, an external additive for adjusting the softening temperature of the paraffin is added to the paraffin in proportion and stirred evenly.

[0014] Furthermore, it also includes a hydrogel water-blocking agent filled in the gaps of the steel wool ball. The preparation process of the hydrogel water-blocking agent is as follows: first, sodium alginate and polyvinyl alcohol are dissolved separately and then mixed, the pH value of the mixed solution is adjusted to weak acidity, and then reacted with polyethylene glycol diglycidyl ether to prepare a multi-block copolymer, methanol is added to precipitate the two polymers at the same time to generate a mixture of the two particles, and then mixed with triethanolamine borate and calcium lactate microcrystals to prepare a high-strength interpenetrating network hydrogel water-blocking agent that is sensitive to both calcium ions and borate ions.

[0015] Furthermore, the structural formula of the multi-block copolymer is as follows:

[0016]

[0017] Furthermore, the preparation of the hydrogel water plugging agent comprises the following steps in sequence:

[0018] S1. Add 15g of sodium alginate to 500mL of distilled water in batches, dissolve it by ultrasonic oscillation, filter it through a sand core funnel, collect the filtrate and set it aside; add 5g of polyvinyl alcohol to 100g of distilled water in batches, heat it to 95°C under stirring, continue stirring for 3 hours, dissolve it, cool it to room temperature, filter it through a sand core funnel, collect the filtrate and set it aside; then mix the two filtrates, ultrasonically oscillate for 2 hours, heat it to 60°C, and slowly drop polyethylene glycol diglycidyl ether under rapid stirring for 5 hours. After the drop is complete, continue stirring and reacting for 3 hours, cool it to room temperature, adjust the pH value to 5.0, slowly add 200ml of methanol, precipitate a white solid powder, filter it, wash it with methanol 3 times, dry it and set it aside;

[0019] S2, heat 0.5g of triethanolamine borate to 50°C, then add 10g of calcium lactate microcrystals with a particle size of 0.03mm to 0.05mm, mix with ultrasonic oscillation for 1 hour to allow triethanolamine borate to be fully adsorbed on the surface and pores of calcium lactate particles, cool to room temperature, and obtain a light yellow solid powder for use;

[0020] S3. The white solid powder obtained in S1 and the light yellow solid powder obtained in S2 were mixed and stirred for 1 hour to obtain a solid powder.

[0021] Compared with the prior art, the present invention has achieved the following beneficial effects: 1. The steel wool is compressed into a smaller spherical shape for easy delivery; after the paraffin melts naturally underground, the steel wool returns to its original shape and its volume can expand 8 to 27 times, accumulating in the leakage channel to form a bridging structure that is not easily washed away.

[0022] 2. The filling material is a multi-block gel water plugging agent which is sensitive to both calcium ions and borate radicals and is prepared with alginate, polyvinyl alcohol, polyethylene glycol diglycidyl ether, triethanolamine borate and calcium lactate microcrystals as main raw materials. It has strong temperature resistance and high strength and can selectively plug the water-producing layer of oil wells.

[0023] 3. Based on the prepared multi-block polymer, the GG segment (guluronic acid) of alginate that simultaneously complexes calcium ions and the 1,3-propylene glycol segment of polyvinyl alcohol that complexes borate ions selectively complex calcium ions and borate ions respectively; as calcium lactate hydrolyzes calcium ions and the original calcium ions in the formation water, triethanolamine borate hydrolyzes borate ions. Through the two complexing effects, the GG segment in the alginate block in the water plugging agent is complexed with calcium ions, and the 1,3-propylene glycol segment is complexed with borate ions to form a high-strength hydrogel. The gel has high strength, strong temperature resistance, and exhibits excellent water plugging ability. DETAILED DESCRIPTION

[0025] In order to make the technical means, creative features, objectives and effects of the present invention easier to understand, the present invention is further described below in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them.

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0027] The expansion plugging material for crack or cave leakage of the present invention comprises an elastic plugging sphere, which adopts an elastic steel wire ball as a skeleton. After compression, the diameter is reduced to 1 / 2 to 1 / 3 of the original diameter. According to the volume formula V=(πD^3) / 6, the volume can expand 8 to 27 times after restoration.

[0028] At the same time, paraffin is used to wrap elastic steel wool to form a ball shape for easy delivery. Since paraffin has the characteristics of solidification at low temperature and melting at high temperature, after being delivered to the bottom of the well, the paraffin can melt at a certain wellbore temperature. After melting, the elastic steel wool wrapped inside is exposed, and its volume expands to 8 to 27 times its original volume, accumulating in the leakage channel to form a bridging structure that is not easily washed away.

[0029] The production process of the elastic leak-proof sphere: select steel wool of appropriate specifications; heat and melt the paraffin, add external additives in proportion, and stir evenly; then soak the steel wool in the melted paraffin liquid, and use a spherical mesh mold to compress it into a ball shape. After the paraffin cools to room temperature and solidifies, take it out together with the mold, and demold it after cooling to obtain the elastic leak-proof sphere.

[0030] The deeper the well, the higher the temperature. The approximate average geothermal gradient of the earth's crust is 25°C per kilometer. The geothermal gradient varies from region to region. The softening point of paraffin is about 54°C. In view of the different formation temperatures at different depths of leakage points, by adding admixtures to paraffin, different types and proportions of admixtures are used to obtain a variety of product series with softening points between 54°C and 150°C to adapt to plugging operations in different regions and well depths.

[0031] At the same time, by adding different types and proportions of weighting materials to paraffin, spherical plugging products with different densities are obtained and used in drilling fluids with different densities. If the drilling fluid density is higher, the density of the selected spherical plugging material should also be higher, which is more conducive to sinking to the target well section.

[0032] After the elastic plugging ball is passed into the wellbore, it can freely roll down to the leakage channel by its own weight and can be used in the well inclination section between 0 and 60 degrees.

[0033] The spherical plugging materials reach the leakage channel and accumulate. After standing for 0.5 to 1.5 hours, as the paraffin gradually softens, the steel wool gradually releases the compression force, the volume recovers, and they squeeze each other to effectively block the leakage channel.

[0034] Since most leakage channels are irregular and have rough surfaces, steel wool can easily hang on the walls of the leakage channels, further increasing the adhesion and improving the strength and stability of the bridge.

[0035] The spheres can be made into different sizes to be used for different degrees of leakage and wellbores of different diameters.

[0036] After the spherical plugging material reaches the leakage channel, as the temperature rises, the paraffin melts, and the elastic steel wool wrapped inside is exposed, and the volume expands to 8 to 27 times its original size, accumulating in the leakage channel to form a bridging structure that is not easily washed away; then the hydrogel water plugging agent is injected as a filling material to fill the gaps between the steel wool balls to improve the success rate of plugging.

[0037] Preparation Example 1 of Hydrogel Water Blocking Agent

[0038] S1. Add 15g sodium alginate (Mn=15000-17000) in batches to 500mL distilled water, dissolve under ultrasonic oscillation, filter through a sand core funnel, collect the filtrate and set aside; add 5g polyvinyl alcohol (model: 1792) in batches to 100g distilled water, heat to 95°C under stirring, continue stirring for 3 hours, dissolve, cool to room temperature, filter through a sand core funnel, collect the filtrate and set aside; then mix the two filtrates, oscillate ultrasonically for 2 hours, heat to 60°C, and slowly drop polyethylene glycol diglycidyl ether (MN=500) under rapid stirring for 5 hours. After the drop is complete, continue stirring and react for 3 hours, cool to room temperature, adjust the pH value to 5.0, slowly add 200ml methanol, precipitate a white solid powder, filter, wash with methanol 3 times, dry and set aside;

[0039] S2, heat 0.5g of triethanolamine borate to 50°C, then add 10g of calcium lactate microcrystals with a particle size of 0.03mm to 0.05mm, mix with ultrasonic oscillation for 1 hour to allow triethanolamine borate to be fully adsorbed on the surface and pores of calcium lactate particles, cool to room temperature, and obtain a light yellow solid powder for use;

[0040] S3. The white solid powder obtained in S1 and the light yellow solid powder obtained in S2 were mixed and stirred for 1 hour to obtain a solid powder.

[0041] Preparation Example 2 of Hydrogel Water Blocking Agent

[0042] The solid powder sample prepared by S3 in Example 1 was accurately weighed, dissolved in clean water with stirring, and suspensions with drug concentrations of 0.5%, 1.0%, 1.5% and 2.0% were prepared. The above suspensions were then placed in sealed cans, reacted at 60°C for 1 day, 3 days and 5 days, respectively, cooled, and taken out to measure the elongation at break and tensile strength of the gels generated at different reaction times, as shown in Table 1.

[0043] Table 1 Elongation at break and tensile strength of gels generated from sample solutions of different concentrations at 60°C

[0044]

[0045] Preparation Example 3 of Hydrogel Water Blocking Agent

[0046] The solid powder sample prepared by S3 in Example 1 was accurately weighed, dissolved in clean water by stirring to prepare a suspension with a drug concentration of 1.5%, placed in a sealed jar, and gelled and aged at 250°C for 3 days, 5 days and 7 days, respectively, cooled, taken out, and the gel strength after different aging times was measured, as shown in Table 2.

[0047] Table 2 Anti-aging ability of gels generated by samples at 250℃

[0048]

[0049] Preparation Example 4 of Hydrogel Water Blocking Agent

[0050] The solid powder sample of S3 in Example 1 was accurately weighed, added to clean water, stirred and dispersed, and prepared into a 1.5% suspension. Artificial simulated cores with similar porosity were placed in an incubator at 60°C for 12 hours; the permeability of the cores before treatment was measured; then the above suspensions with different PVs were reversely injected into the cores, and then kept at 60°C for 3 days; the permeability of the cores after treatment with different dosages of agents was measured, as shown in Table 3.

[0051] Table 3 Core plugging rate after treatment with different dosages of reagents

[0052] Cumulative displacement volume Core pressure difference Initial permeability Blockage rate PV MPa mxDV % 0.1 1.55 2603 80.3 0.3 2.03 2615 88.2 0.5 3.85 2588 94.6 0.7 4.09 2606 95.8 1 7.35 2608 99.5

[0053] The above is only a preferred embodiment of the present invention, which shows and describes the basic principles, main features and advantages of the present invention, but does not limit the scope of patent protection of the present invention. Those skilled in the art should understand that the present invention is not limited by the above embodiments. In addition to the above embodiments, the present invention may have other implementation modes without departing from the spirit and scope of the present invention. The present invention may also have various changes and improvements, and all technical solutions formed by equivalent substitution or equivalent transformation fall within the scope of protection required by the present invention. The scope of protection required by the present invention is defined by the attached claims and their equivalents. The technical features not described in the present invention can be realized by or using existing technologies, which will not be repeated here.

Claims

1. An expansion plugging material for crack or cave leakage, comprising an elastic plugging sphere, characterized in that: The elastic leak-stopping sphere adopts an elastic steel ball as a skeleton, and after the diameter of the elastic steel ball is compressed to 1 / 2 to 1 / 3 of the natural state, it is sealed in paraffin.

2. The expansion plugging material for crack or cave leakage according to claim 1, characterized in that: The preparation method of the elastic leak-proof sphere is as follows: select steel wool balls of appropriate specifications, heat and melt paraffin, then immerse the steel wool balls in the melted paraffin liquid, and use a spherical mesh mold to compress them into a spherical shape. After the paraffin cools to room temperature and solidifies, take them out together with the mold, and demold them after cooling.

3. The expansion plugging material for crack or cave leakage according to claim 2, characterized in that: Add external additives for adjusting the softening temperature of the paraffin wax in proportion to the paraffin wax, and stir evenly.

4. The expansion plugging material for crack or cave leakage according to claim 1, 2 or 3, characterized in that: It also includes a hydrogel water-blocking agent filled in the gaps of the steel wool ball. The preparation process of the hydrogel water-blocking agent is as follows: first, sodium alginate and polyvinyl alcohol are dissolved separately and then mixed, the pH value of the mixed solution is adjusted to weak acidity, and then reacted with polyethylene glycol diglycidyl ether to prepare a multi-block copolymer, methanol is added to precipitate the two polymers at the same time to generate a mixture of the two particles, and then mixed with triethanolamine borate and calcium lactate microcrystals to prepare a high-strength interpenetrating network hydrogel water-blocking agent that is sensitive to both calcium ions and borate ions.

5. The expansion plugging material for crack or cave leakage according to claim 4, characterized in that: The structural formula of the multi-block copolymer is as follows:

6. The expansion plugging material for crack or cave leakage according to claim 4, characterized in that: The preparation of the hydrogel water plugging agent comprises the following steps in sequence: S1. Add 15g of sodium alginate to 500mL of distilled water in batches, dissolve it by ultrasonic oscillation, filter it through a sand core funnel, collect the filtrate and set it aside; add 5g of polyvinyl alcohol to 100g of distilled water in batches, heat it to 95°C under stirring, continue stirring for 3 hours, dissolve it, cool it to room temperature, filter it through a sand core funnel, collect the filtrate and set it aside; then mix the two filtrates, ultrasonically oscillate for 2 hours, heat it to 60°C, and slowly drop polyethylene glycol diglycidyl ether under rapid stirring for 5 hours. After the drop is complete, continue stirring and reacting for 3 hours, cool it to room temperature, adjust the pH value to 5.0, slowly add 200ml of methanol, precipitate a white solid powder, filter it, wash it with methanol 3 times, dry it and set it aside; S2, heat 0.5g of triethanolamine borate to 50°C, then add 10g of calcium lactate microcrystals with a particle size of 0.03mm to 0.05mm, mix with ultrasonic oscillation for 1 hour to allow triethanolamine borate to be fully adsorbed on the surface and pores of calcium lactate particles, cool to room temperature, and obtain a light yellow solid powder for use; S3. The white solid powder obtained in S1 and the light yellow solid powder obtained in S2 were mixed and stirred for 1 hour to obtain a solid powder.

Citation Information

Patent Citations

  • Controllable cross linked gel water blockage plugging material

    CN101353569A

  • Gel plugging agent as well as preparation method and application thereof

    CN106520089A

  • Self-healing gel leakage-proof agent while drilling under covalent bond-non-covalent bond composite action and preparation method and application thereof

    CN113943558A

  • Plugging agent containing modified elastic framework material

    CN114250065A

  • High-strength anti-freezing concrete and preparation method thereof

    CN115849827A